PERAN HUKUM EKONOMI SYARIAH DALAM MENDORONG PERDAMAIAN, KEADILAN EKONOMI SERTA TOLERANSI - Jumiati; Samsul Arip; Raihan Aflah; Rizal Maulana (STKIP Subang, 2024)
Sharia economic law, as an integral part of Islamic teachings, plays a significant role in shaping a just and peaceful social order. Sharia principles, which include justice, transparency, and social responsibility, have great potential in promoting peace, economic justice, and interfaith tolerance. This study aims to examine the role of Sharia economic law in this context through literature analysis and case studies. The findings show that the implementation of Sharia economic principles can reduce economic and social disparities, promote a fairer distribution of wealth, and enhance harmonious relationships between communities. These findings are expected to provide insights for the development of more inclusive and equitable economic policies in various countries Keywords: Sharia Economic Law, Peace, Economic Justice, Tolerance, Wealth Distribution.